Model Matematika Penyebaran CVEV (Citrus vein enation virus) pada Tanaman Jeruk Nipis Melalui Serangga Kutu Daun - Yani, Fitri; Arnellis, Arnellis (UNIVERSITAS NEGERI PADANG, 2023)
Citrus vein enation virus is a virus that attacks lime plants. This virus can cause swelling of the veins of the leaf veins like clumps that are spread irregularly on the underside of the leaves resulting in decreased yields and short-lived plants. This virus is spread by aphids. This research was conducted with the aim of knowing the shape of the mathematical model for the spread of the Citrus vein enation virus and interpreting the research results from the mathematical model. This research uses basic research types and descriptive methods. From the results of the study it was found that the mathematical model of the spread of the Citrus vein enation virus was in the form of a system of differential equations and the interpretation of the model obtained 2 equilibrium points including the equilibrium point which is asymptotically stable because it obtained which is 0.1502685768 which means the virus can disappear within a certain time and the equilibrium point which is asymptotically stable because it gets which means 1.502685768 which means the virus will spread in time long.